PROJECT-BASED BEAUTYPRENEURSHIP: MODEL PEMBELAJARAN UNTUK MENUMBUHKAN JIWA WIRAUSAHA DIGITAL MAHASISWA TATA RIAS - Ririn Amaliah Putri Sarah; Melissha Gemiyolla Irsal; Hanifa Ginelvi; Indri Yani; Laila Ramadani; Wandini Zahra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to analyze the effectiveness of the Project-Based Beautypreneurship model in enhancing digital entrepreneurship skills of third-semester Vocational Beauty students. This research employed a quasi-experimental design with experimental and control groups. The subjects consisted of 59 students, divided into an experimental group (30 students) and a control group (29 students). Data collection instruments included digital entrepreneurship skill tests (pretest and posttest), learning activity observation sheets, and student response questionnaires. The results indicated that the implementation of Project-Based Beautypreneurship significantly improved students’ digital entrepreneurship skills. The experimental group’s mean pretest score was 56.8, which increased to 85.4 in the posttest, while the control group’s mean score increased from 55.9 to 72.1. The N-Gain analysis showed a high improvement in the experimental group (0.67) compared to the control group (0.38). Student learning activities in the experimental group reached 88 percent, higher than the control group at 74 percent. Student responses towards the learning model revealed an average score of 3.56 (very good), while the control group scored 2.98 (good). These findings suggest that the Project-Based Beautypreneurship model is effective in enhancing digital entrepreneurship competence, active engagement, creativity, and independent learning among Vocational Beauty students. This model provides authentic learning experiences that are highly relevant to the demands of the digital beauty industry. The study implies that this model can serve as an innovative alternative in vocational education, particularly in developing students’ entrepreneurial skills and digital competencies